Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai Upt Dinlutkan Kabupaten Rembang - Bayu Laksono, Puryantoro; Dwi Ilhami, Susanti (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
Rembang Regency is one of the areas with a coastline of 76 kilometers and has abundant marine products. UPT Dinlutkan Rembang Regency is a government agency responsible for managing marine potential and maintaining its sustainability. The research that has been conducted aims to obtain evidence and analysis of transformational leadership style, work motivation, and organizational commitment to employee performance. The data collection technique used is the questionnaire method. The data testing method uses reliability testing and validity testing, while the data analysis technique uses multiple linear regression analysis using the R² test. The variable measurement technique uses a Likert scale. The population in this study were all employees of UPT TPI Dinlutkan Rembang Regency totaling 167 employees, while the sample taken was 63 respondents, 30 male and 33 female. The type of data used is subject data. From the results of the study it is known that transformational leadership style has a significant positive effect on performance, work motivation has a positive but insignificant effect on performance and organizational commitment has a positive but insignificant effect on performance. The results of the determination test show that the variables of transformational leadership style, work motivation and organizational commitment can explain employee performance by 30.6%.